The comparison between two different exercise training programs on the mobilization of endothelial progenitor cells in patients with chronic heart failure. (25th November 2020) - Kourek, C; Psarra, K; Alshamari, M; Delis, D; Mitsiou, G; Ntalianis, A; Panagopoulou, N; Papadopoulos, C; Nanas, S; Karatzanos, E
Abstract: Background: Vascular endothelial dysfunction is an underlying pathophysiological feature of chronic heart failure (CHF). Endothelial progenitor cells (EPCs) are being used as an index of vascular endothelial function. Cardiac rehabilitation (CR) programs have been shown to stimulate the mobilization of EPCs in CHF patients. However, the effect of different exercise training programs on the EPCs in CHF patients has not been investigated. Purpose: The purpose of the study was to assess the effect of 2 different exercise training programs on the mobilization of EPCs in patients with CHF and investigate if there were differences between them. Methods: Forty-four consecutive patients (35 males) with stable CHF [mean±SD, Age (years): 56±10, EF (%): 33±8, Peak VO2 (ml/kg/min): 18.4±4.4] enrolled a 36-session CR program and they were randomized in one exercise training protocol; either high-intensity interval training (HIIT) or HIIT combined with muscle strength (COM). Venous blood was drawn at rest before and after the CR program. Five circulating endothelial populations were identified and quantified by flow cytometry (Table 1). EPCs values are expressed as cells/million enucleated cells in medians (25th-75th percentiles). Results: In both HIIT and COM groups, the mobilization of all circulating endothelial populations increased after the CR program (p<0.05, Table 1). However, there was no difference in the mobilization of EPCs between HIIT and COM groups (p>0.05, Table 1). Conclusion: A 36-session cardiac rehabilitation program increases the mobilization of endothelial progenitor cells in patients with chronic heart failure. High-intensity interval exercise training and HIIT combined with muscle strength have similar beneficial effect on endothelial progenitor cells, and therefore on vascular endothelial function. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): Co-financed by Greece and the European Union (European Social Fund- ESF) through the Operational Programme "Human Resources Development, Education and Lifelong Learning" in the context of the project